The Effect of Audit Quality on Real Earnings Management: Evidence from Jordan - Alqudah, Mamoun M. A. (Journal of Ecohumanism, 2024)
The purpose of the current study is to examine whether audit quality is capable of restricting real earnings management in a developing country such as Jordan. The fixed effect method was used to study the association between two audit quality (audit fees and audit firm size), and cash flow from operations (CFO), discretionary expenditure (DISX), and production cost (PROD) as proxies of real earnings management, for the industrial and service firms listed on the Amman Stock Exchange (ASE) during the period 2014-2023. Using 740 firm-year observations, the results showed that the audit fees (AFEE) are significantly and negatively related to cash flow from operations (CFO) and discretionary expenditure (DISX), and also significantly and positively related to production cost (PROD). Meanwhile, the result showed that the existence of audit firm size (B4) has a negative and significant effect on cash flow from operations (CFO) and production cost (PROD), and a positive and significant effect on discretionary expenditure (DISX). Further, for the control variables, the results showed that the firm size (FSIZE) has an insignificant effect on all model variants of real earnings management (REM). Meanwhile, financial leverage (LEV) has a negative effect on all model variants of real earnings management (REM). Thus, these findings provide shreds of evidence for all the regulators, investors, and executives in Jordan due to the significant impact on public policies and interest to the regulators and standard setters.